Bedside detection of awareness in the vegetative state: a cohort study - Cruse, Damian; Chennu, Srivas; Chatelle, Camille; Bekinschtein, Tristan A; Fernández-Espejo, Davinia; Pickard, John D; Laureys, Steven; Owen, Adrian M (The Lancet (British edition), 2011)
Patients diagnosed as vegetative have periods of wakefulness, but seem to be unaware of themselves or their environment. Although functional MRI (fMRI) studies have shown that some of these patients are consciously aware, issues of expense and accessibility preclude the use of fMRI assessment in most of these individuals. We aimed to assess bedside detection of awareness with an electroencephalography (EEG) technique in patients in the vegetative state. This study was undertaken at two European centres. We recruited patients with traumatic brain injury and non-traumatic brain injury who met the Coma Recovery Scale-Revised definition of vegetative state. We developed a novel EEG task involving motor imagery to detect command-following—a universally accepted clinical indicator of awareness—in the absence of overt behaviour. Patients completed the task in which they were required to imagine movements of their right-hand and toes to command. We analysed the command-specific EEG responses of each patient for robust evidence of appropriate, consistent, and statistically reliable markers of motor imagery, similar to those noted in healthy, conscious controls. We assessed 16 patients diagnosed in the vegetative state, and 12 healthy controls. Three (19%) of 16 patients could repeatedly and reliably generate appropriate EEG responses to two distinct commands, despite being behaviourally entirely unresponsive (classification accuracy 61–78%). We noted no significant relation between patients' clinical histories (age, time since injury, cause, and behavioural score) and their ability to follow commands. When separated according to cause, two (20%) of the five traumatic and one (9%) of the 11 non-traumatic patients were able to successfully complete this task. Despite rigorous clinical assessment, many patients in the vegetative state are misdiagnosed. The EEG method that we developed is cheap, portable, widely available, and objective. It could allow the widespread use of this bedside technique for the rediagnosis of patients who behaviourally seem to be entirely vegetative, but who might have residual cognitive function and conscious awareness. Medical Research Council, James S McDonnell Foundation, Canada Excellence Research Chairs Program, European Commission, Fonds de la Recherche Scientifique, Mind Science Foundation, Belgian French-Speaking Community Concerted Research Action, University Hospital of Liège, University of Liège.